Clinical Usefulness of Atrioventricular Coupling in Cardiovascular Disease - Yang Lan, Li Zhenyi, Chen Ya, Chen Anni, Wang Xinqi, Jin Lin, Li Zhaojun (Advanced Ultrasound in Diagnosis and Therapy)
Atrioventricular Coupling (AV-Coupling) refers to the functional coordination between atrial and ventricular systole and diastole in the heart. Currently, the primary method for evaluating AV-Coupling is through the left atrioventricular coupling index (LACI), measured using imaging techniques. A higher LACI indicates a greater mismatch between the volumes of left atrium and left ventricle at the end of ventricular diastole, reflecting a more significant impairment of left AV-Coupling. AV-Coupling plays a vital role in the pathophysiology and progression of cardiovascular diseases. Therefore, early and accurate assessment of AV-Coupling is essential for evaluating a patient’s condition, guiding clinical decisions, stratifying risk, and determining prognosis. This review aims to summarize the physiological mechanisms and evaluation methods of AV-Coupling, as well as its clinical significance in various cardiovascular diseases.